Smoke Kings : a novel - Mayfield, Jahmal (Melville House, 2024)
"Nate Evers, a young black political activist, struggles with rage as his people are still being killed in the streets...When his little cousin is murdered, Nate shuns the graffiti murals, candlelight vigils, and Twitter hashtags that are commonplace after these senseless deaths. Instead, he leads 3 grief-stricken friends on a mission of retribution, kidnapping the descendants of long-ago perpetrators of hate crimes, confronting the targets with their racist lineages, and forcing them to pay reparations to a community fund"--